Age-related atrial fibrillation: is there a role for the gut microbiome? - Michael Li; Eduardo Castañeda; Robert M. Lust (Exploration of Cardiology)
Age-related atrial fibrillation (AF) is a common condition that has yet to be fully understood, with mechanisms to explain its development under investigation. Notably, cellular senescence, cardiac fibrosis, coronary ischemia, cardiac valvular disease, autonomic dysfunction, channelopathies, and immune system remodeling are processes that have been seen to occur with aging and ample evidence has shown their association with the development of AF. Despite robust therapeutic approaches, the incidence of AF continues to rise, suggesting that the dynamic, multi-faceted interactions leading to AF are incompletely understood. One of the newer mechanisms currently being investigated is the gut microbiome. Although more research is needed to understand its impact on the development of age-related AF and targets for therapies, the gut microbiome is a promising new avenue of research that may provide future benefits in AF prophylaxis or enhanced management. As the field works towards developing this knowledge, there are important questions to answer as to the optimal role of potential gut microbiome targeting therapies and their potential risks versus the benefits they provide. This commentary first summarizes the currently understood mechanisms contributing to age-related AF, which is then followed by an analysis of the current work investigating the role of the gut microbiome in the development of age-related AF, and concludes by highlighting notable questions to consider in future work on the role of the gut microbiome and its relationship to age-related AF.